2015
DOI: 10.1016/j.socscimed.2015.06.030
|View full text |Cite
|
Sign up to set email alerts
|

‘Healthy anorexia’: The complexity of care in disordered eating

Abstract: This paper examines how contemporary understandings of 'health' and 'care' are engaged with and practiced by women with disordered eating. Based on findings from an Australian study investigating why people with disordered eating are reluctant to engage with treatment services (March 2012 to March 2015), we demonstrate how young women use elements of a 'health habitus' and 'care' to rationalise and justify their practices. Moving beyond Foucauldian theories of self-discipline and individual responsibility we a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
59
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(61 citation statements)
references
References 28 publications
0
59
0
Order By: Relevance
“…Communication and perception of risks, as traditionally recognized, are flanked by communication and induction of apparently neutral behavior that can behave as true risk factors for disease. The strong pressure towards practices aimed at optimizing physical fitness and dietary methods aimed at healthy foods often involves forms of orthorexia[18]; such strategies are widely used to gain and maintain niches of food and fitness markets. All this would be irrelevant, except that, as in the case of prevention of obesity and fatty liver, and probably also in the field of atherosclerotic, neurodegenerative and cancer diseases, dietary caloric intake and a sedentary lifestyle are not the only factors exerting independent synergistic effects[6].…”
Section: Introductionmentioning
confidence: 99%
“…Communication and perception of risks, as traditionally recognized, are flanked by communication and induction of apparently neutral behavior that can behave as true risk factors for disease. The strong pressure towards practices aimed at optimizing physical fitness and dietary methods aimed at healthy foods often involves forms of orthorexia[18]; such strategies are widely used to gain and maintain niches of food and fitness markets. All this would be irrelevant, except that, as in the case of prevention of obesity and fatty liver, and probably also in the field of atherosclerotic, neurodegenerative and cancer diseases, dietary caloric intake and a sedentary lifestyle are not the only factors exerting independent synergistic effects[6].…”
Section: Introductionmentioning
confidence: 99%
“…24,43,44 The present study can help to clear those limits and know more deeply the condition of living concerned about healthy eating.…”
Section: Continued Tablementioning
confidence: 84%
“…19 And as data concerning gender and age, although the orthorexic disposition occurs more in men and in different age groups, it continues to be proportionally superior in women, 20,21 being, in short, a risk factor of mental and physical health. 22 In a similar way, there is bibliographic testimony that supports the condition of orthorexia as a lifestyle in which fits the appearance (esthetics), and the cultivation and processing of food (nature or essence); the purchase of non-toxic food (organic, ecologic, pure, without pesticides or other artificial products) and a thorough examination of its components; 23 food and ritual practices according to a logic of care that also engages the family; 24 illusory sense of security (belief in preventing disease), a need for absolute control over oneself, "a hidden conformism" to achieve a culturally accepted model as beautiful; perfectionism towards oneself and oriented to others, fruit of self-demand and social constructions;…”
mentioning
confidence: 95%
“…Brown, Tanner, and Padley () examined the experience of individuals suffering from a surgical site infection and found that the emotional capital gained from stoicism led patients to avoid seeking the help they needed when they experienced an infection. Musolino, Warin, Wade, and Gilchrist () explored disordered eating in women. Healthy eating was commonly associated with the embodiment of the “healthism habitus” or the choices made surrounding the consumptions of certain foods, which signified the conformity to the dominant habitus (thinness associated with feminine beauty).…”
Section: Discussionmentioning
confidence: 99%